2018
DOI: 10.1002/2018gl077015
|View full text |Cite
|
Sign up to set email alerts
|

Nightside Detection of a Large‐Scale Thermospheric Wave Generated by a Solar Eclipse

Abstract: The generation of a large‐scale wave in the upper atmosphere caused by a solar eclipse was first predicted in the 1970s, but the experimental evidence remains sparse and comprises mostly indirect observations. This study presents observations of the wind component of a large‐scale thermospheric wave generated by the 21 August 2017 total solar eclipse. In contrast with previous studies, the observations are made on the nightside, after the eclipse ended. A ground‐based interferometer located in northeastern Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 24 publications
2
52
0
1
Order By: Relevance
“…A very strong upward plasma motion with speeds up to 40 m/s higher than normal was observed for ∼2 hr after the maximum eclipse (19-21 UTC). This upward motion could be potentially caused by two contributing factors: (1) immediate (at supersonic speed) ionospheric and thermospheric heating due to recovery from the eclipse, and (2) enhanced southward and eastward (directed towards maximum shadow) wind as would be anticipated in the eclipse-induced colder thermosphere (Harding et al, 2018). This upward motion could be potentially caused by two contributing factors: (1) immediate (at supersonic speed) ionospheric and thermospheric heating due to recovery from the eclipse, and (2) enhanced southward and eastward (directed towards maximum shadow) wind as would be anticipated in the eclipse-induced colder thermosphere (Harding et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A very strong upward plasma motion with speeds up to 40 m/s higher than normal was observed for ∼2 hr after the maximum eclipse (19-21 UTC). This upward motion could be potentially caused by two contributing factors: (1) immediate (at supersonic speed) ionospheric and thermospheric heating due to recovery from the eclipse, and (2) enhanced southward and eastward (directed towards maximum shadow) wind as would be anticipated in the eclipse-induced colder thermosphere (Harding et al, 2018). This upward motion could be potentially caused by two contributing factors: (1) immediate (at supersonic speed) ionospheric and thermospheric heating due to recovery from the eclipse, and (2) enhanced southward and eastward (directed towards maximum shadow) wind as would be anticipated in the eclipse-induced colder thermosphere (Harding et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Neutral wind velocity derived from nighttime OI 630.0 nm (red line) emission measurements by a Fabry‐Perot interferometer in Brazil showed perturbations in neutral winds far from the path of the 21 August 2017 eclipse. Global‐scale simulations using an ultraviolet obscuration mask that mimicked the 21 August 2017 eclipse's effect on the upper atmosphere successfully predicted the measured changes (using the red line) in neutral wind qualitatively (Harding et al, ).…”
Section: Introductionmentioning
confidence: 86%
“…Besides geomagnetic storms, solar eclipses are also known to excite AGWs (e.g., Chimonas & Hines, 1970a;Liu et al, 1998) that alter the IT system (Harding et al, 2018;Lin et al, 2018). Liu et al (1998) conclude that the ionospheric perturbations that they observed using ionosondes during the total solar eclipse of 24 October 1995 were most likely due to plasma upflow and downflow induced by rapid temperature increase immediately following the eclipse.…”
Section: Introductionmentioning
confidence: 99%
“…However, Harding et al (2018) done with the Thermosphere-Ionosphere-Mesosphere-Electrodynamics (TIME)-GCM. However, Harding et al (2018) done with the Thermosphere-Ionosphere-Mesosphere-Electrodynamics (TIME)-GCM.…”
Section: Comparison To Observationsmentioning
confidence: 99%